2019
DOI: 10.1039/c9ra04465e
|View full text |Cite
|
Sign up to set email alerts
|

PHB/PCL fibrous membranes modified with SiO2@TiO2-based core@shell composite nanoparticles for hydrophobic and antibacterial applications

Abstract: Schematic illustration of the synthesis of SiO2@TiO2-based core@shell composite nanoparticles (top) and antibacterial hydrophobic behavior of fibrous membranes (bottom).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Another important aspect of wound healing is the permeability to air [ 71 ]. The introduction of Hmi made a significant contribution to the control of the breathability of nonwoven fabric ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another important aspect of wound healing is the permeability to air [ 71 ]. The introduction of Hmi made a significant contribution to the control of the breathability of nonwoven fabric ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, TiO 2 synthesis followed the procedure reported by Lin et al with minor modification. 45 Then, 0.485 μL Tween-80 was added into 100 mL ethanol : H 2 O (19 : 1, v/v). Another solution containing 10 mL of TBT and 10 mL of ethanol was injected into the mixture of Tween-80, ethanol, and H 2 O at a rate of 0.5 mL min −1 and constant pressure using a funnel.…”
Section: Methodsmentioning
confidence: 99%
“…Lin et al fabricated an electrospun PHB‐PCL nanofiber substrate to be used in packaging applications and modified the nanofiber surface with SiO 2 ‐TiO 2 composite nanoparticles produced by the stöber method. It was observed that the prepared PCL‐PHB/SiO 2 ‐TiO 2 composite membrane had excellent hydrophobicity and antibacterial activity with a water contact angle of 144° ± 1° 46 . In another study, PAN‐SiO 2 nanofibers were produced to be used in the separation of oil–water emulsion mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the prepared PCL-PHB/SiO 2 -TiO 2 composite membrane had excellent hydrophobicity and antibacterial activity with a water contact angle of 144 ± 1 . 46 In another study, PAN-SiO 2 nanofibers were produced to be used in the separation of oil-water emulsion mixtures. First, PAN nanofibers were produced and then the fibrous surface was modified with SiO 2 nanoparticles produced by the sol-gel method.…”
Section: Introductionmentioning
confidence: 99%